Forecasting the Ensuing Impact of 3G on Business Practices in India: An Exploratory Analysis - Sharma, Amalesh; Borah, Sourav Bikash (Indian Journal of Marketing, 2011)
Dramatic changes in mobile technology and worldwide push towards the third-generation technologies (3Gs) have started to shake the business world. Competitive advantage, core competency, etc. have become buzz words in the business world. Many questions around 3G are occupying the premier role in the strategic decision-making process. In this paper, the authors have attempted to forecast the probable impacts of 3G technology on the business practices in India. Authors have discussed the probable impacts of 3G on promotional and advertisement practices of the companies, changes expected in the practicing business models and dos and don’ts for companies to sustain in competitions. Authors have also discussed the technical part of the 3G technology and the challenges it will create for proper implementation. The paper attempts to examine some analytical perspective of 3G technology over 2G. The probable effects of 3G are forecasted both from customers and companies’ point of view, and a conceptual framework is developed, relating 3G and its impact on various business verticals. The authors have pointed out a few strategies for the companies, which can be beneficial for the firms to sustain in the competitions. According to the Federation of Indian Chambers of Commerce and Industry (FICCI), in India, the 3G subscriber base is expected to hit 90 million by 2013, accounting for 12% of the overall wireless user base. This is definitely an opportunity for the corporate world to tap a part of the market. The paper explains some of the exclusive market based phenomenon expected because of 3G.